Prospects of Integrating Caviaculture and Fish Farming in the Western Region of Cameroon - MIÉGOUÉ Emile; Davy TAGNING ZEBAZE Pégis; EFOLE EWOUKEM Thomas; TENDONKENG Fernand; LEMOUFOUET Jules; NGANYO KOMGUEP Ronald; Etienne TEDONKENG PAMO et (International Journal of Aquaculture Research and Development, 2019)
This study was conducted within three months at the University of Dschang Research and Application Farm (5°44’-5°36’ et 5°44’-5°37’ LN ; 10°06’-9°94’ et 10°06’-9°85’ LE). The main objective was to evaluate the integration perspectives of caviaculture and fishery. Specifically, the study was aimed at evaluating the production of guinea pig dungs, its bromatological composition and appreciating the nitrogen/phosphorus ratio in other to determine the adequate quantities of manure for a proper fertilization of fish ponds. Hence, 96 guinea pigs weighing averagely 390 ± 110g each were randomly distributed into two comparable lots (floor covered with litter and floor without litter) and were subjected to 8 feeds (5 grasses and 3 legumes). Each lot had 6 repetitions of 8 individuals. The animals were fed three times daily within 30 days. The dungs of guinea pigs were collected after three days between 6 and 8am during the experimental period. They were then selected and weighed using and electric balance of 0.1g sensitivity. At the end of the study, the following results were obtained: a guinea pig of 390 ± 110 g in confinement produced between 51.7 ± 0.4 to 60.5 ± 0.7g (fresh weight) of dung per day. The bromatological analysis of these dungs showed that they are made of organic material (80.0%), dry matter (94.3%), crude protein (10.7%), ash (19.9%) and nitrogen (22.7%). These results attesting the richness of these dungs helped in estimating the quantities (103.4g to 206.8g) of dung/day/100m2 for the breeding of 2 to 4 guinea pigs per fish pond of 100 m2 for an integrated breeding (guinea pig-fish).
Keywords: caviaculture